THE RUSSIAN FEDERATION IN CONFLICT IN THE POST-SOVIET SPACE: NAGORNO-KARABAKH (Вісник: Міжнародні відносини, 2025)
In 1991, Nagorno-Karabakh, with the support of Armenia and the Russian Federation, declared independence from Azerbaijan. This led to hostilities that lasted until 1994. The armed conflict ended with the signing of the Bishkek Protocol on an armistice and ceasefire, but armed clashes periodically broke out between the parties. To mediate in the settlement of the conflict, the Minsk Group was established in 1992, consisting of 19 member states of the Conference on Security and Cooperation in Europe (now the OSCE), which was co-chaired in 1997 by the Russian Federation, France and the United States. As one of the most interested players, the Russian Federation sought to play a leading role in the Nagorno-Karabakh settlement, both because it contributed to the conclusion of the Ceasefire Agreement between Azerbaijan, Nagorno-Karabakh, and Armenia in 1994, and because of its geopolitical and geoeconomic interests in the South Caucasus region. It was thanks to the imperial policy of the Russian Federation that the Armenian-Azerbaijani conflict in Nagorno-Karabakh became “frozen” and one that for more than three decades played a central role in the new geopolitics in Eurasia, affecting the regional security of the Caucasus and the entire Middle East.Methods. The main methodological approaches to the study of the Russian Federation’s policy in the former USSR were historical, political science, and geopolitical. It is the latter that views the Russian Federation’s policy in the post-Soviet space as an attempt to restore its geopolitical and geoeconomic influence through such tools as mediation, peacekeeping, and economic expansion. This approach helps to clarify the true motives of the Kremlin’s participation in the so-called conflict resolution process, as well as to understand the reasons for the Russian Federation’s geopolitical defeat in Nagorno-Karabakh.Results. The inability of international mediators to offer a political and diplomatic way to resolve the conflict, compounded by the parties’ distrust and the desire of neighboring countries to take advantage of the complexity of the Karabakh problem to resolve their own geostrategic issues, prompted the Azerbaijani authorities to mobilize significant financial resources to re-equip the army and prepare for a force scenario of returning the temporarily occupied territories (TOT). The Armenian authorities, on the other hand, relying on the traditional support of the Russian Federation, reinforced by Yerevan’s participation in the CSTO, which was supposed to guarantee Moscow’s allied support in the event of an armed conflict with Azerbaijan, have become a de facto vassal of the Kremlin and have practically lost their international subjectivity. Taking advantage of the Russian Federation’s involvement in the civil conflict in Syria and the weakening of the Russian army’s combat capability in the long-running Russian-Ukrainian war, as well as the military support of Turkey, Baku conducted military operations in 2020 and 2023, which resulted in the restoration of Azerbaijan’s territorial integrity. This happened despite the Russian Federation’s policy in Karabakh, which was based on Moscow’s desire to keep the Karabakh conflict in a “settled” state, playing on the irreconcilable contradictions of its participants. After Azerbaijan regained control of Karabakh and the authorities of the self-proclaimed NKR announced the cessation of the unrecognized state entity, more than 100,000 Karabakh Armenians left the region. Currently, Azerbaijan and Armenia are negotiating a peace agreement, for the first time without Russian mediation. On August 8, 2025, at a trilateral meeting at the White House between Azerbaijani President Ilham Aliyev and Armenian Prime Minister Nikol Pashinyan and US President Donald Trump, an agreement was signed to normalize Azerbaijani-Armenian relations. An agreement that could completely change the South Caucasus, the development of which is hampered by closed borders, long-standing ethnic conflicts and the Kremlin's imperial policy. The framework document, aimed at achieving a concrete path to peace, envisages the creation of a strategic transit corridor through the South Caucasus, which will connect the main territory of Azerbaijan with the Nakhichevan exclave via Armenia. The United States, within the framework of the agreements, will receive from Armenia exclusive rights to develop this corridor, which will be called the "Trump Path for International Peace and Prosperity", known by the acronym TRIPP. Thus, the United States will exercise control over a strategic transport hub in the region bordering Russia, Turkey and Iran. Thanks to TRIPP, the United States will strengthen its geopolitical influence in the South Caucasus, displacing such traditional players as the Russian Federation and France and exerting geopolitical pressure on Iran. Tehran opposed the United States' laying of a corridor through the territory of Armenia connecting Azerbaijan with the Republic of Nakhichevan. They believe that in this way NATO will get closer to the northern Iranian territories. This means that the settlement of the Nagorno-Karabakh problem is far from exhausting the problems of geopolitical rivalry in the South Caucasus.Conclusions. The restoration of the territorial integrity of Azerbaijan as a result of the 44-day war of 2020 and the anti-terrorist operation of 2023 in Nagorno-Karabakh showed the weakness of the Russian Federation and the possibility of its displacement from the South Caucasus, and in the future, its decomposition as a state. The return of the TOT under Baku's control means that to solve this task, such factors as the political will of the state leadership to return the TOT, the consolidation of the country's material and military resources to achieve the goal, a favorable international situation and the presence of at least one powerful strategic ally, which for Azerbaijan is Turkey, must be present. This, in short, is the recipe for victory over the shadow of the "evil empire", which still remains the Russian Federation. For Ukraine and the civilized world. The geopolitical confrontation in Nagorno-Karabakh, the main actors of which were the Russian Federation, the USA, France and Turkey, brought victory to the Western countries and a fiasco to the Russian Federation. But the great geopolitical game in the South Caucasus, intensified by the recent discovery of significant hydrocarbon deposits in the Caspian region, which was reflected in the implementation of projects for laying strategic transport highways such as the Baku-Tbilisi-Ceyhan oil pipeline and the Baku-Supsa gas pipeline, continues. Since the Russian Federation, weakened by the war in Ukraine, has far from exhausted its capabilities in the region and, under favorable circumstances, is capable of changing the geopolitical situation in the South Caucasus in its favor. This is evidenced, among other things, by the attempt of Russian revenge in Georgia. Keywords: Nagorno-Karabakh, Russian Federation, Azerbaijan, Armenia, “frozen” conflict, post-Soviet space, geopolitical interests, imperial syndrome.
Keywords: Nagorno-Karabakh; Russian Federation; Azerbaijan; Armenia; “frozen” conflict; post-Soviet space; geopolitical interests; imperial syndrome.